2010
DOI: 10.4049/jimmunol.0903300
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Activated Microglia/Macrophage WAP Domain Protein, AMWAP, Acts as a Counter-Regulator of Proinflammatory Response

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 70 publications
2
55
0
1
Order By: Relevance
“…Moreover, they demonstrated that AMWAP expression is rapidly induced by ligands for TLR2, -4, and -9 and IFN-g, thereby reducing proinflammatory cytokine expression (Karlstetter et al, 2010b).…”
Section: Microglia In Degenerating Diseasesmentioning
confidence: 99%
“…Moreover, they demonstrated that AMWAP expression is rapidly induced by ligands for TLR2, -4, and -9 and IFN-g, thereby reducing proinflammatory cytokine expression (Karlstetter et al, 2010b).…”
Section: Microglia In Degenerating Diseasesmentioning
confidence: 99%
“…We have previously characterized the macrophage/microglia WAP domain protein (AMWAP) as a regulator of pro-inflammatory response 37,38 . AMWAP transcription is rapidly induced in microglia from different retinal disease mouse models, including inherited photoreceptor dystrophies and different light challenge paradigms 7,32,33,39 .…”
Section: Development Of the Protocolmentioning
confidence: 99%
“…AMWAP was recently identified as a counter-regulator of the proinflammatory response in macrophages. 36 However, its role in diabetes or any other disease has never been examined. Figure 8L).…”
Section: Il-17a Administration Suppresses Podocyte and Tubular Epithementioning
confidence: 99%
“…However, AMWAP significantly reduced albuminuria and glomerulosclerosis (Figure 9, E-G). Because AMWAP is known to have anti-inflammatory activity 36 by turning macrophages to the M2 phenotype, we analyzed M2 marker expression in vehicle-and AMWAP-treated control and diabetic mouse kidney. Vehicle-treated diabetic mouse kidney showed increased proinflammatory M1 marker (IL-6 and IL-1b) ( Epithelial Cell-Specific Overexpression of IL-17A or IL-17F Is Sufficient to Suppress Diabetic Nephropathy in Mice We have created IL-17A and IL-17F overexpressing mice using the epithelial cellspecific E-cadherin promoter.…”
Section: Il-17a Administration Suppresses Podocyte and Tubular Epithementioning
confidence: 99%